Analisis Administrasi Data Beasiswa Jabar Future Leader Scholarship (JFLS) dalam Peningkatan Mutu Pendidikan - Robiah, Siti; Yoseptry, Ricky; Indah, Nur; Wandani, Wandani; Kusnadi, Andini Angraeni (STKIP PGRI SITUBONDO, 2024)
The Ministry of Education West Java Province provides scholarships for residents of Western Java called Jabar Future Leader Scholarship (JFLS) which is included in the Yuknis Regulations of Governor (Pergub) West Java and is based on the decision of the Governor of West Jawa Number: 305/HK.02.03/PSMA (JFLS). This research uses qualitative research, where the researcher intends to analyze the data on the Jabar Future Leader Scholarship (JFLS) from the start of the planning to the evaluation. The method used is a qualitative method with an analytical-descriptive approach. The JFLS program is designed to be accessible to the public, so its management or implementation requires an effective and efficient management system. In line with the main objective of the program, which is the dissemination of education, in its socialization there is an effort that utilizes information and technology, like the use of information media such as websites, social media platforms, and YouTube channels. Exhibitions and learning opportunities for students who have difficulty paying for education in particular the JFLS Graduate Program to the region as well as improving the quality of education in the West Java Territory. Inter-agency collaboration with scholars can be a source of inspiration and quality improvement. It is suggested that the institution motivate students more, so that students who take the scholarship program can improve their achievements in both academic and non-academic fields.